2021
DOI: 10.1002/mbo3.1145
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved N‐terminal domain in the first module of ACV synthetases

Abstract: The l‐δ‐(α‐aminoadipoyl)‐l‐cysteinyl‐d‐valine synthetase (ACVS) is a trimodular nonribosomal peptide synthetase (NRPS) that provides the peptide precursor for the synthesis of β‐lactams. The enzyme has been extensively characterized in terms of tripeptide formation and substrate specificity. The first module is highly specific and is the only NRPS unit known to recruit and activate the substrate l‐α‐aminoadipic acid, which is coupled to the α‐amino group of l‐cysteine through an unusual peptide bond, involving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…Furthermore, the adenylation reaction occurs on the side chain (δ) carbonyl group, resulting in a noncanonical peptide bond between l -α-Aaa and the second substrate l -cysteine (Iacovelli et al., 2020 ; Tahlan et al., 2017 ). In a recent study, a novel conserved domain was identified at the N-terminus of the first module of ACVS, with a partial homology to condensation domains (Iacovelli et al., 2021 ). Though its function remains yet to be elucidated, it appears essential for the adenylation of l -α-Aaa and therefore for the functionality of the entire enzyme.…”
Section: Penicillium Rubens and Natural Productsmentioning
confidence: 99%
“…Furthermore, the adenylation reaction occurs on the side chain (δ) carbonyl group, resulting in a noncanonical peptide bond between l -α-Aaa and the second substrate l -cysteine (Iacovelli et al., 2020 ; Tahlan et al., 2017 ). In a recent study, a novel conserved domain was identified at the N-terminus of the first module of ACVS, with a partial homology to condensation domains (Iacovelli et al., 2021 ). Though its function remains yet to be elucidated, it appears essential for the adenylation of l -α-Aaa and therefore for the functionality of the entire enzyme.…”
Section: Penicillium Rubens and Natural Productsmentioning
confidence: 99%
“…102 Furthermore, CRISPR/Cas has facilitated Natural Product Reports Review testing of short deletions to investigate putative condensation domains within b-lactam precursor NRPS enzymes in Penicillium rubens. 103 Studying secondary metabolites by gene knockout in the native host is also a robust complement to heterologous expression when the metabolic products are suspected to be artifacts of the heterologous host machinery. For example, CRISPR/Cas knockouts of core and accessory biosynthetic genes of the thermolides BGC in Thermomyces dupontii claried key biosynthetic steps that had previously been incorrectly identi-ed by heterologous expression.…”
Section: Reviewmentioning
confidence: 99%
“…CRISPR elements can be delivered as ribonucleoproteins preassembled in vitro, or as genetic elements that are expressed by the host. The AMA1 (autonomous maintenance in Aspergillus) sequence from A. nidulans supports autonomous vector replication in several filamentous fungal species (Fierro et al, 1996;Aleksenko and Clutterbuck, 1997), and thus vectors encoding this sequence have been extensively used for gene delivery and expression purposes, as well as delivering CRISPR components (Fuller et al, 2015;Nødvig et al, 2015;Pohl et al, 2016;Salazar-Cerezo et al, 2020;Iacovelli et al, 2021b). Single vector-based CRISPR/Cas9 genome editing systems have been previously developed for several filamentous fungal species (Song et al, 2019).…”
Section: Crispr-mediated Genome Editingmentioning
confidence: 99%